The effectiveness of aesthetic values ​​in Typographic design (Journal of the College of Basic Education, 2022)
Poster accomplish Jamali has controls imposed by its diversity, depending on the substance posed by the case, which contained structure of the executive, in the midst of these data are aesthetic values ​​difficult to determine its elements and its structure and its systems formal manner be convincing to all but Aalaqa rejection of one, and because the label placed renewed, and as the work of my design esthetic it is subject to the techniques and different directions secreted by the artist, and evolve according to the evolution of time and the evolution of society in all its aspects and accordingly poses a researcher his questions in defining the research problem, namely: 1 -What are the variations and variations theory dealing with the values ​​of the beauty of the poster? 2 -What are the mechanisms of activation of aesthetic values ​​in the label and upgrading it? Where the researcher found justification logical addresses that problem the study and scrutiny through his research, which is marked: ((effective aesthetic values ​​in graphic design)). It Has been reached on a set of results from the most important: 1- that the figure in the design, in particular, is characterized by the values ​​of the formal unity of the integrated express the unity of material. 2- sources shape design built the second area, which confirms that the source of the shape design is inherent in the mind of the designer of any Hidden as forms for products design beyond Amaho uncommon in nature, where showed the adoption of the design on the second theory to the effect.